ANALISIS PENGARUH PENGETAHUAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA BANDAR LAMPUNG - Suhendar Suhendar (ITB AAS Indonesia Surakarta, 2023)
The purpose of this study was to examine and analyze the effect of tax knowledge on SME taxpayer compliance in Bandar Lampung City. The research method used is the explanatory method. The population in this study were SMEs in Bandar Lampung City with a total sample of 100 respondents. The sampling technique used is simple random sampling. The data collection technique used is a questionnaire using a Likert instrument measuring scale. The data analysis technique used is Simple Linear Regression. The results showed that there was a positive and significant effect on the level of tax knowledge on the level of compliance of SME taxpayers in Bandar Lampung City. Thus, to improve taxpayer compliance in Bandar Lampung City, the government and society need to increase tax knowledge.